2018
DOI: 10.1002/acm2.12510
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐low dose CT colonography with automatic tube current modulation and sinogram‐affirmed iterative reconstruction: Effects on radiation exposure and image quality

Abstract: ObjectiveTo assess the radiation dose and image quality of ultra‐low dose (ULD)‐CT colonography (CTC) obtained with the combined use of automatic tube current (mAs) modulation with a quality reference mAs of 25 and sinogram‐affirmed iterative reconstruction (SAFIRE), compared to low‐dose (LD) CTC acquired with a quality reference mAs of 55 and reconstructed with filtered back projection (FBP).MethodsEighty‐two patients underwent ULD‐CTC acquisition in prone position and LD‐CTC acquisition in supine position. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…We used the terms ULD and SD patient radiation dose, and the estimated mean effective dose levels were 0.9 and 3.6 mSv for ULD and SD, respectively. The terms SD and ULD have no universal definition, but our radiation dose levels are in approximate agreement with those of others in CTC ( 20 ) and urinary low-dose CT examinations ( 21 ) . In a study by Lambert et al .…”
Section: Discussionsupporting
confidence: 85%
“…We used the terms ULD and SD patient radiation dose, and the estimated mean effective dose levels were 0.9 and 3.6 mSv for ULD and SD, respectively. The terms SD and ULD have no universal definition, but our radiation dose levels are in approximate agreement with those of others in CTC ( 20 ) and urinary low-dose CT examinations ( 21 ) . In a study by Lambert et al .…”
Section: Discussionsupporting
confidence: 85%
“…The ultra-low-dose technique employed in this study reduced the tube voltage by 33% and halved the tube current when compared to the standard-dose protocol. Furthermore, the algorithm of adaptive iterative dose reduction used in this study effectively worked on noise reduction and improvement of image quality [ 9 , 25 , 26 ]. These technical means reduced the effective radiation by 99.29%.…”
Section: Discussionmentioning
confidence: 99%
“…These software reconstructions techniques are Sinogram-Affirmed Iterative Reconstruction (SAFIRE) and a conventional filtered back projection. These techniques allowed the use of even lower doses of radiation than the conventional low dose (LD) protocol named ultra-low dose (ULD) with maintained image quality[ 5 , 24 , 30 ]. In 2018, a study evaluating the ULD protocol's diagnostic value in detecting polyps[ 31 ] showed that the ULD protocol lowers the effective dose up to 63.2% compared to LD protocol (0.98 mSv for ULD and 2.69 mSv for LD).…”
Section: Radiation Induced Risksmentioning
confidence: 99%
“…In contrast, the 2D option is the routine CT examination technique. Polyp detection was also comparable, with no significant difference in detection rate and polyp measurement for LD and ULD protocols[ 30 ]. Therefore if iterative reconstruction methods (the software option in almost all modern CT scanners) were included during the scanning, there was no significant image quality degradation with ULD-CTC compared with LD-CTC.…”
Section: Radiation Induced Risksmentioning
confidence: 99%
See 1 more Smart Citation